In-ICU Outcomes of Critically Ill Patients in a Reference Cameroonian Intensive Care Unit: A Retrospective Cohort Study - Edgar Mandeng Ma Linwa; Charles Binam Bikoi; Joel Tochie Noutakdie; Emmanuel Ndoye Ndo; Jean Moise Bikoy; Charlotte Eposse Ekoube; Raissa Fogue Mogoung; Igor Simo Ghomsi; Michael Ngenge Budzi; Esther Eleonore Ngo Linwa; Martin Geh Meh; David Mekolo (Critical Care Research and Practice)
Introduction. Mortality rate amongst critically ill patients admitted to the intensive care unit (ICU) is disproportionately high in sub-Saharan African countries such as Cameroon. Identifying factors associated with higher in-ICU mortality guides more aggressive resuscitative measures to curb mortality, but the dearth of data on predictors of in-ICU mortality precludes this action. We aimed to determine predictors of in-ICU mortality in a major referral ICU in Cameroon. Methodology. This was a retrospective cohort study of all patients admitted to the ICU of Douala Laquintinie Hospital from 1st of March 2021 to 28th February 2022. We performed a multivariable analysis of sociodemographic, vital signs on admission, and other clinical and laboratory variables of patients discharged alive and dead from the ICU to control for confounding factors. Significance level was set at p<0.05. Results. Overall, the in-ICU mortality rate was 59.4% out of 662 ICU admissions. Factors independently associated with in-ICU mortality were deep coma (aOR = 0.48 (0.23–0.96), 95% CI, p=0.043), and hypernatremia (>145 meq/L) (aOR = 0.39 (0.17–0.84) 95% CI, p=0.022). Conclusion. The in-ICU mortality rate in this major referral Cameroonian ICU is high. Six in 10 patients admitted to the ICU die. Patients were more likely to die if admitted with deep coma and high sodium levels in the blood.